Experience sharing about hotels on TripAdvisor: motivation and preferences of brazilian tourists - Pereira Viana, Jean; Feder Mayer, Verônica; Rodrigues de Souza Neto, Valério (Marketing & Tourism Review, 2020)
This paper analyzed the dynamics of review postings of brazilian consumers about services provided by hotels on TripAdvisor. The methodology adopted was qualitative and the method used was content analysis, with the collection and codification of 371 reviews of hotels. The results showed a good perception about the quality of the services provided, with motivations related to social benefits and assistance being the most identified in the reviews. Some unfavorable aspects were also found in some reviews, such as the perception of unfair prices. Other relevant aspects were also observed and recommendations were made both for management and for future research.